The European seabass (Dicentrarchus labrax) innate immunity and gut health are modulated by dietary plant-protein inclusion and prebiotic supplementation. Issue 60 (January 2017) - Azeredo, Rita; Machado, Marina; Kreuz, Eva; Wuertz, Sven; Oliva-Teles, Aires; Enes, Paula; Costas, Benjamín
Abstract: Inclusion of prebiotics in aqua feeds, though a costly strategy, has increased as a means to improve growth. Still, its effects on health improvement are not fully disclosed. Regarding their immunestimulatory properties, research has focused on carbohydrates such as fructooligosaccharides and xylooligosaccharides demonstrating their modulatory effects on immune defences in higher vertebrates but few studies have been done on their impact on fish immunity. Replacing fish meal (FM) by plant protein (PP) sources is a current practice in the aquaculture business but their content in antinutrients is still a drawback in terms of gut well-functioning. This work intends to evaluate the short-term effect (7 or 15 days feeding the experimental diets) on juvenile European seabass ( Dicentrarchus labrax ) immune status of dietary i) replacement of FM by PP sources; ii) prebiotics supplementation. Six isoproteic (46%) and isolipidic (15%) diets were tested including a FM control diet (FMCTRL), a PP control diet (PPCTRL, 30 FM:70 PP) and four other diets based on either FM or PP to which short-chain fructooligosaccharides (scFOS) or xylooligosaccharides (XOS) were added at 1% (FMFOS, PPFOS, FMXOS, PPXOS). The replacement of FM by PP in the diets induced nitric oxide (NO) and lysozyme production, while immunoglobulins (Ig), monocytes percentage and gut interleukin 10 (IL10) gene expression were inhibited. Dietary scFOS supplementation inhibited total bactericidal activity and neutrophils relative percentage regardless protein source and increased plasma NO and thrombocytes percentage in fish fed FM-based diets, while monocytes percentage was increased in PPFOS-fed fish. XOS supplementation down-regulated immune gene expression in the gut while it partly enhanced systemic response. Inconsistency among results regarding FM replacement by PP-based ingredients exposes the need for further research considering both local and systemic responses. Distinct outcomes of prebiotic supplementation were highlighted reflecting sight-specific effects with no clear interaction with protein source. Highlights: The immunomodulatory effects of prebiotics and plant protein sources were tested. Vegetable protein sources both activate and suppress different immune parameters. Xylooligosaccharides inhibited gut immune defences, regardless of protein source. Fructooligosaccharides effects suggest a slight stimulation of cell dynamics.